Examining the presence of bullying in students with mild intellectual disability and typically developing secondary school students with an intellect of sound development (Academic Journal of Internal Affairs, 2024)
Aim: The aim of this study is to investigate the possible presence of bullying among secondary school students with mild intellectual disabilities. Data from the focus group were compared with data from the secondary school age group with an intellectually healthy population (control group). The aim of our study was to find out the frequency and regularity of bullying in the sample. The research also sought to find out whether the subjects in the focus and control groups recognise the fact of abuse, its different forms, and which persons are the most frequent perpetrators of abuse. We also looked at how often they suffer abuse and whether there are people in their environment to whom they turn for help in this context.Methodology: In our empirical study we conducted a paper-based questionnaire survey.Findings: Thirty-six per cent of typically developing pupils with an intellectually healthy child and 36 per cent of pupils with mild intellectual disabilities also identified possible causes of victimisation. 86 percent of the focus group and 92 percent of the control group had experienced some form of abuse. 66 per cent of typically developing pupils with a sound intellect and 50 per cent of pupils with a mild intellectual disability had a good recognition of verbal abuse.Value: The research highlights the high incidence of bullying in educational institutions today, which not only affects typically developing minors, but also the group of people with intellectual disabilities to a significant extent. The research points the way for future research on this issue in relation to other disability groups.
Keywords: abuse, intellectual disability, victimisation, behavioural attitudes